2017
DOI: 10.1007/s13197-016-2449-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing spray drying conditions of sour cherry juice based on physicochemical properties, using response surface methodology (RSM)

Abstract: In this study, the effects of main spray drying conditions such as inlet air temperature (100-140°C), maltodextrin concentration (MDC: 30-60%), and aspiration rate (AR) (30-50%) on the physicochemical properties of sour cherry powder such as moisture content (MC), hygroscopicity, water solubility index (WSI), and bulk density were investigated. This investigation was carried out by employing response surface methodology and the process conditions were optimized by using this technique. The MC of the powder was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
16
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 25 publications
7
16
0
7
Order By: Relevance
“…In general, the freeze-dried powders had higher bulk density by approximately 11% when compared to the spray-dried products. In the case of maltodextrin and the mixture of maltodextrin and inulin, similarly to Bhusari et al [41], Goula and Adamopoulos [43], and Moghaddam et al [44], the bulk density of cranberry powders decreased within the increase in the concentration of the carrier. Tontul and Topuz [35] suggested that such behavior of the powders might be connected to the prevention of sticking by selected carriers.…”
Section: Concentration Of Carriersupporting
confidence: 54%
“…In general, the freeze-dried powders had higher bulk density by approximately 11% when compared to the spray-dried products. In the case of maltodextrin and the mixture of maltodextrin and inulin, similarly to Bhusari et al [41], Goula and Adamopoulos [43], and Moghaddam et al [44], the bulk density of cranberry powders decreased within the increase in the concentration of the carrier. Tontul and Topuz [35] suggested that such behavior of the powders might be connected to the prevention of sticking by selected carriers.…”
Section: Concentration Of Carriersupporting
confidence: 54%
“…Equation (2) As the inlet temperature increased, the moisture content reduced, thereby increasing the solubility. [25,26] At lower TS, the solubility decreased when the flow rate increased ( Figure 2), which demonstrated that the lower flow rate (2.5 ml/min) was favorable for obtaining a higher solubility. Increasing the feed flow rate reduces the outlet temperature, thereby increasing the difference between inlet and outlet temperatures, resulting in a greater remaining moisture content in the product.…”
Section: Response Surface Analysis Of Solubilitymentioning
confidence: 91%
“…The greater temperature gradient between the medium and particles resulted in a quicker transfer of heat to the particles, thus reducing the content of moisture. [24,25] Among the experimental runs, the highest moisture content was observed for 10% TS, 9.87 ml min −1 flow rate, and 160°C inlet temperature ( Table 2). It was observed that the experimental results and the predicted values of moisture content derived from Equation (1) at a different set of runs were comparable ( Table 2).…”
Section: Response Surface Analysis Of Moisture Contentmentioning
confidence: 99%
“…As shown in Table 1, compared to the solubility of nonencapsulated SPH (S-1, F-1), the change with encapsulation with SPH (S-2, S-3, F-2, F-3) is very small. Although the solubility of SPI is not good, MD has excellent solubility, and the solubility of the sample increases with the increase of MD content [26,27]. Grabowski et al [28] also found that the solubility of sweet potato powder increased with the amount of maltodextrin increased.…”
Section: Comparison Of Properties Of Different Dry Samplesmentioning
confidence: 99%